The Effect of Service Quality, Physical Environment and Restaurant Images on Consumer Satisfaction through Perception of Value - Heri Setiawan; Jalaludin Sayuti (Faculty of Economics, Universitas Sriwijaya, 2019)
This research uses a quantitative approach using numbers, starting from data collection, data interpretation, and discussion of the results of the analysis. This type of research is causal research, which is research that shows the causal relationship between independent variables on the dependent variable in addition to measuring the strength of the relationship between these variables through hypothesis testing. The research method used in this study is a survey method. The population in this study are consumers who have enjoyed food in local restaurants in Palembang. The type of sampling used is purposive sampling. To meet the minimum requirements for a path analysis tool, 240 study respondents were taken with the provisions of the selection of consumers who have enjoyed food at a local restaurant in Palembang with certain considerations. The results show that service quality and restaurant image, both have a linear relationship with perceived value, while physical environment is found to have no effect on perceived value. It is also found that service quality, physical environment, restaurant image and perceived value, all have a significant effect on consumer satisfaction.